Low-molecular-weight metabolite systems chemistry - Hadacek, Franz; Bachmann, Gert (Frontiers in Environmental Science, 2015)
Low-molecular-weight metabolites (LMWMs) comprise primary or central and a plethora of intermediary or secondary metabolites, all of which are characterized by a molecular weight below 900 Dalton. The latter are especially prominent in sessile higher organisms, such as plants, corals, sponges and fungi, but are produced by all types of microbial organisms too. Common to all of these carbon molecules are oxygen, nitrogen and, to a lesser extent, sulfur, as heteroatoms. The latter can contribute as electron donators or acceptors to cellular redox chemistry and define the potential of the molecule to enter charge-transfer complexes. Furthermore, they allow LMWMs to serve as organic ligands in coordination complexes of various inorganic metals as central atoms. Especially the transition metals Fe, Cu and Mn can catalyze one electron reduction of molecular oxygen, which results in formation of free radical species and reactive follow-up reaction products. As antioxidants LMWMs can scavenge free radicals. Depending on the chemical environment, the same LMWMs can act as pro-oxidants by reducing molecular oxygen. The cellular regulation of redox homeostasis, a balance between oxidation and reduction, is still far from being understood. Charge-transfer and coordination complex formation with metals shapes LMWMs into gel-like matrices in the cytosol. The quasi-polymer structure is lost usually during the isolation procedure. In the gel state, LMWMs possess semiconductor properties. Also proteins and membranes are semiconductors. Together they can represent biotransistor components that can be part of a chemoelectrical signaling system that coordinates systems chemistry by initiating cell differentiation or tissue homeostasis, the activated and the resting cell state, when it is required. This concept is not new and dates back to Albert Szent-Györgyi.